Ensino de leitura e de escrita a adultos com deficiência intelectual matriculados na Educação de Jovens e Adultos - Silva, Érika Rímoli Mota da (Universidade Federal de São Carlos, 2017)
The present study aimed to evaluate the acquisition of reading and writing skills in adults with intellectual disability who attended the Education of Young and Adults (EJA) program through a computerized reading and writing teaching procedure. Three adults with intellectual disability, aged 26-37, participated in the study. A pre-and post-test design of the reading and writing repertoire was used. Participants were exposed to the individualized teaching program, conducting teaching sessions interspersed with periodic progress assessments. The teaching program was composed of five units with four teaching steps each (except the first containing five steps and the last, which contained three steps). Each step taught three vowel-consonant words and their corresponding syllables. The results showed that the three participants presented meaningful gains in reading, writing and in the two-way relations between figure and printed word (equivalence relations), with teaching and recombination words, performing fewer repetitions of teaching steps. In reading, P1 and P2 presented low performance in pre-test and P3 presented approximately 70% of correct responses. In writing, in the first test, the two participants presented null performance and P3 presented low performance (27% and 33% of correct responses in writing skill by composition and manuscript, respectively). In the post-test, P1 showed 100% of correct responses in reading and 100 and 93% of correct respondes in writing by composition and manuscript; P2 presented 93,3% of correct responses in reading and 86,7 and 80% of correct responses in writing by composition and manuscript; and P3 did not undergo the final evaluation; however, the assessments throughout the procedure showed P3’s progress in the skills assessed. The results showed that this educational program can benefit adults with IDs enrolled in regular education in order to acquire initial reading and writing repertoires. Future studies should investigate complementary conditions for the generalization of these findings to different situations and environments.
Teaching of reading and writing to intellectual disability adults enrolled in Education for Youth and Adults
Keywords: Educação de Jovens e Adultos; Ensino de leitura e de escrita; Youth and Adult Education; Equivalence of stimuli; Educação especial; Deficiência intelectual; Special education; Intellectual disability; Teaching reading and writing; Equivalência de estímulos; CIENCIAS HUMANAS::EDUCACAO; CIENCIAS HUMANAS::EDUCACAO::ENSINO-APRENDIZAGEM; CIENCIAS HUMANAS::EDUCACAO::TOPICOS ESPECIFICOS DE EDUCACAO